The The Role of the OCEAN Personality Model in Moderating the Determinants on the Quality of Local Budget Utilization - Rizka Amaliah; Majid, Jamaluddin; Syariati, Namla Elfa (Income Journal: Accounting, Management and Economic Research, 2023)
This study aims to determine the effect of human resource competence, organizational culture, and internal control on the quality of budget utilization with the OCEAN personality model as a moderating variable at the Makassar Public Health Center. This research method is quantitative with a descriptive approach. The population and sample in this study were financial managers at the Makassar Public Health Center. The sampling technique used was purposive sampling. Respondents in this study were financial managers at health centers in 15 districts of Makassar City. The data used in this study is primary data obtained from respondents through a questionnaire survey. This study uses multiple linear regression analysis and moderated regression analysis (MRA) with an analytical approach. The results showed that the competence of human resources, organizational culture, and internal control affect the quality of budget utilization. Furthermore, the OCEAN personality model is able to moderate the competence of human resources and organizational culture on the quality of budget utilization, while the OCEAN personality model is not able to moderate internal control over the quality of budget utilization.